2014
DOI: 10.1128/aem.02544-14
|View full text |Cite
|
Sign up to set email alerts
|

Increased Biofilm Formation by Nontypeable Haemophilus influenzae Isolates from Patients with Invasive Disease or Otitis Media versus Strains Recovered from Cases of Respiratory Infections

Abstract: f Biofilm formation by nontypeable (NT) Haemophilus influenzae remains a controversial topic. Nevertheless, biofilm-like structures have been observed in the middle-ear mucosa of experimental chinchilla models of otitis media (OM). To date, there have been no studies of biofilm formation in large collections of clinical isolates. This study aimed to investigate the initial adhesion to a solid surface and biofilm formation by NT H. influenzae by comparing isolates from healthy carriers, those with noninvasive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
0
22
1
Order By: Relevance
“…After 3 h, the wells were magnetized using a block of 96 magnets in standard microplate format. Under these conditions, microbeads migrate to the center of the well, forming a spot, but bacterial cells attached to the bottom of the well block the migration of the beads and reduce the intensity of the spot (21). Figure 3A shows photographs of wells that were inoculated with sterile broth, JE2 inoculum, or JE2 inoculum supplemented with low-dose amoxicillin and then incubated for 3 h and magnetized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 3 h, the wells were magnetized using a block of 96 magnets in standard microplate format. Under these conditions, microbeads migrate to the center of the well, forming a spot, but bacterial cells attached to the bottom of the well block the migration of the beads and reduce the intensity of the spot (21). Figure 3A shows photographs of wells that were inoculated with sterile broth, JE2 inoculum, or JE2 inoculum supplemented with low-dose amoxicillin and then incubated for 3 h and magnetized.…”
Section: Resultsmentioning
confidence: 99%
“…Under these conditions, free beads migrate to the center of the well, forming a spot. Bacterial cells that attach to the bottom of the well block the migration of the beads and reduce the intensity of the spot (21). The plate was imaged using the BioFilm Control plate reader and analyzed with the accompanying image analysis software.…”
Section: Methodsmentioning
confidence: 99%
“…While this may be appropriate for (large scale) screening purposes, other investigations may require specific hydrodynamic conditions, substratum composition or large quantity of biomass material that the microtiter tray based methods cannot provide. The choice of the device depends on the scientific question and a complete characterization of biofilm formation ability for a strain generally requires combining different approaches (Puig et al, 2014;Renier et al, 2014).…”
Section: Microtiter Platesmentioning
confidence: 99%
“…The speed of initial bacterial adhesion was evaluated by the biofilm ring test on modified 96-well polystyrene plates obtained from BioFilm Control (St. Beauzire, France) as previously described (13). Briefly, bacterial suspensions were mixed with magnetic beads, incubated for 2 or 4 h at 37°C, and placed on a magnetic block.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, we found that especially NTHi strains collected from patients with OM have the ability to form biofilms in vitro (13). This is consistent with in vivo experiments, where biofilms in the ears of chinchillas were associated with bacterial persistence (14).…”
Section: Introductionmentioning
confidence: 99%